Synthesis of Silica-Coated Fe3O4 Nanoparticles by Microemulsion Method: Characterization and Evaluation of Antimicrobial Activity - Goshu Asab; Enyew Amare Zereffa; Teshome Abdo Seghne (International Journal of Biomaterials)
Magnetite and silica-coated magnetite (Fe3O4) nanoparticles (NPs) were synthesized by water-in-oil (W/O) microemulsion method from hydrated ferric nitrate, ferrous sulfate precursors and ammonia a precipitating agent with the assistance of Tween-80 and SDS surfactants. The synthesized materials were characterized by X-ray diffraction, scanning electron microscopy, thermal analyzer, and infrared spectroscopy. X-ray diffraction pattern of Fe3O4 showed that particles were phase pure with a cubic inverse spinel structure and FT-infrared spectra confirmed the presence of Fe-O bond in tetrahedral and octahedral interstitial sites. The crystallite size determined from powder XRD data with Scherer’s equation was in the range of 7.3 ± 0.05 nm–10.83 ± 0.02 nm for uncoated Fe3O4 and 16 ± 0.14 nm for silica-coated Fe3O4 NPs. The SEM micrographs of the uncoated Fe3O4 oxide revealed the agglomeration of the magnetite (Fe3O4) particles. But the silica-coated Fe3O4 oxide exhibited homogeneous distribution of particles with relatively less agglomerate of the particles. The particle size of Fe3O4 NPs slightly increased with the temperature and precursor concentration. The antimicrobial activities of Fe3O4 and silica-coated Fe3O4 nanoparticles were tested against Gram-negative (Escherichia coli and Pseudomonas aeruginosa) and Gram-positive (Staphylococcus aureus and Bacillus subtilis) bacteria. Both Fe3O4 and silica-coated Fe3O4 NPs demonstrated better antimicrobial activities.